Essays on public policies in the brazilian northeast - CALDAS, Renata de Melo (2016)
This dissertation evaluates three different public policies implemented in Brazil with the main objective of reducing regional inequalities and improving life conditions of the poorest region of the country, the Northeast. In the first chapter, I analyze the impact of the Constitutional Financing Program (FNE) on income and employment at municipality level. Data are from the Brazilian demographic censuses and FNE dataset, provided by the Bank of Northeast, for 2000 and 2010. There is a discussion about the inclusion of new municipalities in semi arid delimitation in Brazil. The main argument is that these municipalities would benefit from the FNE, which has better benefits for those inside semi arid area, such as smaller interest rates and longer financing terms and limits. Using difference-in-differences estimation, I analyze the relationship of microcredit program on income or employment, using the Census 2000 as the baseline and the Census 2010 as the post-treatment period. I do not find a relationship of microcredit program on income or employment, and one possible reason for this is the fact that new municipalities are not taking more funding from FNE. The second chapter evaluates the effectiveness of a public irrigation project implemented in Litoral do Camocim e Acaraú micro-region, at Ceará state, in the Northeast region of Brazil. The dataset is based on individual Censuses data of 2000 and 2010, capturing pre and post period of an irrigation project’s implementation in the region, which happened in 2001. Although the literature points to a positive relationship between irrigation and income, I find, in general, a negative and significant impact of irrigation on main wages, total wages and productivity. One of the reasons for this unexpected result is that workers may switch to agricultural sector and become family farmers, who produce for their own consumption. In this way, even though they do not have higher wages, they may be better off in terms of consumption and nutrition. When analyzing the impact on specific products produced at Baixo Acaraú irrigated area, the coefficients are positive and significant at 1%. Finally, the third and last chapter analyzes the impact of intergovernmental transfers on inter and intra-regional inequalities in Brazil. Taking advantage of the discontinuities of the Municipalities Participation Fund (FPM) – an important intergovernmental transfer – this paper uses a regression discontinuity design to identify the causal impact of FPM transfers on regional economic growth rates. I find that an increase in FPM transfer impacts positively on economic growth rate of the poorest region of the country (Northeast) and has no significant impact on the richest region (Southeast), which indicates a decrease in the inter-regional inequality. Nonetheless, I find that the improvements on growth rates achieved by the Brazilian Northeast are driven by the richest municipalities. These results suggest that even though intergovernmental transfers help poor regions catching up intra regional inequalities may increase.